Faktor Pendorong Anggota PATRA Dalam Mendukung Pertanian Organik Di Desa Lombok Kulon Kecamatan Wonosari Kabupaten Bondowoso - Gita Permana; Lenny Widjayanthi (UNEJ e-Proceeding, 2018)
The young farmer-training program known as PATRA (PelatihanAnakTaniRemaja) is a training activity given to adolescents in Lombok Kulon and a solution to the problem of regeneration of labour in agriculture. PATRA members who have participated in the training chose to continue supporting the activities of organic farming. Some of them decided to continue supporting organic farming, while the others didn’t continue their activities on organic farming. Those who support organic farming are incorporated in GAPOKTAN Al-Barokah. This study aimed to determine the reasons of PATRA members in joining the organic farming. The determination of the research area was choosen purposively,namely in Lombok Kulon, Wonosari, Bondowoso. Informant were determined purposively consisting of PATRA, PPL Agriculture, and the Chair of GAPOKTAN were determined as the informants through purposive sampling. Data analyzed used Miles and Huberman Model. Data validation used triangulation of source informant and technique. The results showed that the push factors of PATRA members in joining the organic farming activities were as follows: 1) To full fill their physiological needs; 2) The price of organic rice is higher than unorganic rice, availibility of market, health aspects, and plant resistance towards pest and disease attacks; 3) To gain the opportunities to form relationships with other parties; 4) To express concern of the environmental sustainability; 5) To increase their knowledge and skills.